The Role of Dexa Scan Application in Uremic Patients on Hemodialysis in Ibn-Sina Hemodialysis Center - Hameed Mohamed, Shakir Hameed Mohamed; Naser Haded, Yousif; Ibrahim Latif, Ismail; Methab Athab, Ahmed; Khalid Alwendi , Nabeel (Diyala Journal of Medicine, 2020)
Background: Chronic kidney disease is an international public health problem affecting 5–10% of the world population. As kidney function declines, there is a progressive deterioration in mineral homeostasis, with a disruption of normal serum and tissue concentrations of phosphorus and calcium. Objective: To determine the effect on bone density by dexa scan and mineral derangement in chronic renal failure, by measuring calicium, phosphate, alkaline phosphatase and parathyroid serum ,total serum protein and Albumin levels and to determine bone density by dexa scan of bones. Patients and Methods: Cross sectional study was conducted in 75 patients with chronic renal failure . Blood was taken before dialysis session and measurements of serum calcium, phosphorus, serum alkaline phosphatase, .protein and albumin levels, and dexa scan to measure the bone density in these patients. Results: There was a significant correlation between Hypocalcemia and dexa scan results. Majority of patients had high serum phosphate levels (54.6%).and normal phosphate level in 40% while the hypophosphatemia result 5.33% and mean phosphate level is2.24 mmol/l. Total serum protein mean is 61.51 , 37.33% of them had hypoproteinemia and 62.66 % of them had normal serum protein. There was a significant correlation between dexa scan and vit D level, calcium, alkaline phosphatase, female gender, smoking and body mass index. Conclusion: The current study demonstrated that it can predict the chronic kidney diseases- Metabolic bone disorder from mineral levels before diagnosis by dexa scan.